PENGARUH PEMBERIAN SLOW STROKE BACK MASSAGE (SSBM) TERHADAP PERUBAHAN KUALITAS TIDUR PASIEN STROKE ISKEMIK DI RSUD TAMAN HUSADA BONTANG - Martini, Martini; Frana Andrianur; Amiruddin (Bajang Institute, 2024)
Stroke results in a proportion of poor sleep quality in stroke patients. Poor sleep quality is a predisposing factor for stroke and increases the severity of stroke experienced by patients. The aim of this study was to determine the effect of Slow Stroke Back Massage (SSBM) in Ischemic Stroke patients on sleep quality. This research was carried out at Taman Husada Bontang Hospital. The research design used was quasi-experimental with a pre-test and post-test approach, with a sample size of 16 respondents for each group. The research instrument uses the PSQI (Pittsburgh Sleep Quality Index) questionnaire which has been tested for validity and has a value of ???? 0.05 by assessing 7 items including subjective sleep quality, sleep duration, sleep efficiency, sleep disturbances, sleep latency, sleep dysfunction during the day. , and use of sleeping pills and the score for each question is 0-3. The results of hypothesis testing using the Independent Samples Test obtained p = 0.001 (pValue < 0.05), SSBM has a significant effect on improving the sleep quality of Ischemic Stroke Patients. Researchers suggest providing additional intervention in the form of the Slow Stroke Back Massage (SSBM) technique for patients who experience problems with sleep quality.